Experience with Continuous Infusion Vancomycin Dosing in a Large Pediatric Hospital. (30th April 2018) - Hurst, Amanda L; Baumgartner, Christine; MacBrayne, Christine E; Child, Jason
Abstract : Continuous infusion of vancomycin provides a safe alternative to escalating doses of intermittent infusions to attain a therapeutic vancomycin concentration in pediatric patients. Patients <8 years old require higher total daily doses of continuously infused vancomycin than those ≥8 years of age. Abstract: Background: There is a paucity of data on dosing of continuous infusion of vancomycin (CIV) in pediatric patients, despite it being an attractive treatment option for limiting escalating doses of intermittent infusion of vancomycin. The purpose of this study was to determine the total daily dose of CIV required to attain therapeutic serum vancomycin concentrations (SVCs) in pediatric patients according to age (≥31 days to <2 years, 2 to <8 years, and 8 to <18 years). Methods: We retrospectively evaluated patients who were transitioned from intermittent infusion of vancomycin to CIV between January 2013 and December 2016. Demographic data, vancomycin data (indication, dosing, steady-state SVCs, and time to reach goal SVC), and adverse-effect data (infusion reactions and serum creatinine level) were collected. Results: Of the 240 patients included, 76 had a goal SVC of 10 to 15 µg/mL and 164 had a goal of 15 to 20 µg/mL. The dose of CIV required to reach an SVC of 10 to 15 µg/mL in the youngest age group was 48.4 mg/kg per day versus 45.6 and 39.4 mg/kg per day in the older age groups ( P < .005). The 2 younger age groups of patients with a goal SVC of 15 to 20 µg/mL required 50.2 and 50.6 mg/kg per day, respectively, whereas patients aged ≥8 years required 44.7 mg/kg per day ( P = .008). One patient experienced renal injury, and 1 experienced renal failure. Conclusions: CIV is an effective method for attaining a therapeutic SVC in pediatric patients. Patients <8 years of age require higher dosing than older pediatric patients to reach the goal SVCs of 10 to 15 and 15 to 20 µg/mL.